THE DETERMINANTS AND CORRELATION OF GRADUATE STUDENTS RESEARCH CAPABILITY, INTEREST AND SATISFACTIONS - Cherie B. Orpia (Universitas PGRI Madiun, 2022)
The paper aims to ascertain graduate students' perceived research capability skills at Ilocos Sur Polytechnic State College – Sta Maria, Ilocos Sur, Philippines. Based on the calculated sample size, respondents filled out a structured questionnaire distributed via messaging applications. To illustrate the findings, statistical descriptive were created, and constraints were identified where capability training would be required. The findings indicated that respondents perceived themselves to have a low level of research writing capability in terms of developing the study's framework, developing the methodology, collecting, cleaning, and encoding data, performing data analysis, preparing presentations for poster and oral discussion, and writing the research article for publication. Therefore, an improvement should be addressed through research capability seminars.